Predicting the clinical prognosis of acute ischemic stroke using machine learning: an application of radiomic biomarkers on non-contrast CT after intravascular interventional treatment - Gu, Hongxian; Yan, Yuting; He, Xiaodong; Xu, Yuyun; Wei, Yuguo; Shao, Yuan (Frontiers in Neuroinformatics, 2024)
To develop a radiomic model based on non-contrast CT (NCCT) after interventional treatment to predict the clinical prognosis of AIS (acute ischemic stroke) with large vessel occlusion. Methods: We retrospectively collected 141 cases of AIS from 2016 to 2020, and analyzed the patients' clinical data as well as NCCT data after interventional treatment. Then the total dataset was divided into training and testing set according to subject serial number. The cerebral hemispheres on the infarct side were segmented for radiomics signature extraction. After radiomics signatures were standardized and dimensionality reduction, the training set was used to construct a radiomics model by using machine learning. The testing set was then used to validate the prediction model, which was evaluated based on discrimination, calibration, and clinical utility. Finally, a joint model was constructed by incorporating the radiomics signatures and clinical data.The AUCs of the joint model, radiomics signature, the NIHSS score, and hypertension were 0.900, 0.863, 0.727, and 0.591 respectively in training set. In testing set, the AUCs of the joint model, radiomics signature, the NIHSS score, and hypertension were 0.885, 0.840, 0.721, and 0.590, respectively.Our results provided evidence that using post-interventional NCCT for radiomic model could be a valuable tool in predicting the clinical prognosis of AIS with large vessel occlusion.